Gestão de web rádios: uma proposta de sistema com indicadores estratégicos - Rios, Eduardo Gondim (2016)
In over a hundred years, Brazilian media companies have built a segment capable of producing economic and financial results by entertainment production and information, associated with the learning obtained in the way of managing resources, monetize investments and produce new marketing models. Along the way, the radio market (part of media market) was pioneered in many practices that allowed the segment companies achieve profitability in their operations. The Internet and its advent, however, present themselves as a technological change agent in the form of consuming the radio. Is In this new possibility of radio consumption that arise webradios: new companies in order to produce and broadcast radio content exclusively for the Web. As entrants in the media market, the managers of webradios formulate their strategies for dealing with challenges such as: advertising market, labor costs, investments, financial soundness and audience. The purpose of this work is, from case studies and interviews with experts, understand the strategies of webradios and propose a management system with critical indicators that support this business.